Book review of Visioning a Mi’kmaw Humanities: Indigenizing the Academy. - Downey, Adrian (Comité canadien des étudiants diplômés en éducation, 2018)
This text comprises a book review of Visioning a Mi’kmaw Humanities: Indigenizing the Academy edited by Marie Battiste. The book covers a wide variety of topics including Indigenizing social studies and math education, representations of Mi’kmaw in the Nova Scotia curriculum, Mi’kmaw language resurgence and revitalization efforts, and Mi’kmaw approaches to research and theory in the humanities. This essay highlights three distinct contributions of Mi’kmaw Humanities. First, the book helps frame the conversation around responding to the Truth and Reconciliation Commission’s (TRC) calls to action in the Mi’kmaw philosophy of humanity. Second, it provides practitioners working with Indigenous peoples valuable insight into navigating cultural, epistemic, and linguistic differences. Finally, Mi’kmaw Humanities gives the next generation of Mi’kmaw scholars a firm base from which to assert their intellectual independence.